THE ROLE OF SUBTITLE IN FOREIGN LANGUAGE TEACHING - Bengü Aksu Ataç; Sevtap Günay Köprülü (Informascope, 2018)
Today it is accepted that learning a language by seeing, hearing and by getting to know the culture is a more appropriate approach. In this sense, films in foreign language teaching are important audio-visual tools in terms of reflecting the fineness of the language, culture and customs and traditions, clothes and lifestyle of a community. In language teaching, it is very important to know what words and expressions are used in which context and environment and to pronounce them correctly. Many language learners benefit from this audiovisual tool because of the contributions of films to foreign language learning. Especially in the developing of listening comprehension skills, learners prefer to watch films on foreign language. There are three options: watching the film in its original language without subtitles, watching the film in its original language with subtitles in source language and watching the film in its original language through subtitle translation in target language. In this study, it has been searched which method and the reason English language teaching department students prefer to improve their English language skills. Therefore, the factors that should be considered in the selection of films to be used in foreign language learning, the subtitle as a method of film translation, the place of subtitles in language learning, the positive and negative aspects of film translation with subtitle method have been dealt with and some suggestions have been made. As a research tool, appropriate sampling questionnaire has been distributed to the students and collected data has been analyzed by SPSS program. As a result of the research, students believe that watching films has improved their listening comprehension skills and has a positive contribution to the development of their speaking skills. Thus, they prefer English subtitles more.